Interference of electrons ionized by short laser pulses - Arbo, Diego (2007)
We analyze the two-dimensional momentum distribution of electrons ionized by short laser pulses by solving the time-dependent Schrödinger equation. Lindner et al., [Phys. Rev. Lett. 95, 040401 (2005)] identified oscillations in the electron emission spectrum for ionization by a few-cycle pulse as a time-double slit interference. We extend this analysis to interference fringes in the momentum distributions. For longer pulses we find a complex twodimensional interference pattern that resembles ATI rings at higher energies and displays Ramsauer-Townsend - type diffraction oscillations in the angular distribution near threshold.